Emotional Evaluations from Partners and Opponents Differentially Influence the Perception of Ambiguous Faces - Danyang Ran; Yihan Zhang; Bin Hao; Shuaixia Li (Behavioral Sciences)
The influence of contextual valence and interpersonal distance on facial expression perception remains unclear despite their significant role in shaping social perceptions. In this event-related potential (ERP) study, we investigated the temporal dynamics underlying the processing of surprised faces across different interpersonal distances (partner, opponent, or stranger) and contextual valence (positive, neutral, or negative) contexts. Thirty-five participants rated the valence of surprised faces. An advanced mass univariate statistical approach was utilized to analyze the ERP data. Behaviorally, surprised faces in partner-related negative contexts were rated more negatively than those in opponent- and stranger-related contexts. The ERP results revealed an increased P1 amplitude for surprised faces in negative relative to neutral contexts. Both the early posterior negativity (EPN) and late positive potentials (LPP) were also modulated by contextual valence, with larger amplitudes for faces in positive relative to neutral and negative contexts. Additionally, when compared to stranger-related contexts, faces in partner-related contexts exhibited enhanced P1 and EPN responses, while those in opponent-related contexts showed amplified LPP responses. Taken together, these findings elucidate the modulation of intricate social contexts on the perception and interpretation of ambiguous facial expressions, thereby enhancing our understanding of nonverbal communication and emotional cognition.